Antiretroviral Drugs Regulate Epigenetic Modification of Cardiac Cells Through Modulation of H3K9 and H3K27 Acetylation - Kashyap, Shiridhar; Mukker, Avni; Gupta, Deepti; Datta, Prasun K.; Rappaport, Jay; Jacobson, Jeffrey M.; Ebert, Steven N.; Gupta, Manish K. (Frontiers in Cardiovascular Medicine, 2021)
Antiretroviral therapy (ART) has significantly reduced the rate of mortality in HIV infected population, but people living with HIV (PLWH) show higher rates of cardiovascular disease (CVD). However, the effect of antiretroviral (ARV) drug treatment on cardiac cells is not clear. In this study, we explored the effect of ARV drugs in cardiomyocyte epigenetic remodeling. Primary cardiomyocytes were treated with a combination of four ARV drugs (ritonavir, abacavir, atazanavir and lamivudine), and epigenetic changes were examined. Our data suggest that ARV drugs treatment significantly reduces acetylation at H3K9 and H3K27 and promotes methylation at H3K9 and H3K27, which are histone marks for gene expression activation and gene repression, respectively. Besides, ARV drugs treatment causes pathological changes in the cell through increased production of reactive oxygen species (ROS) and cellular hypertrophy. Further, the expression of chromatin remodeling enzymes was monitored in cardiomyocytes treated with ARV drugs using PCR array. The PCR array data indicated that the expression of epigenetic enzymes was differentially regulated in the ARV drugs treated cardiomyocytes. Consistent with the PCR array result, SIRT1, SUV39H1 and EZH2 protein expression was significantly upregulated in ARV drugs treated cardiomyocytes. Furthermore, gene expression analysis of the heart tissue from HIV+ patients showed that the expression of SIRT1, SUV39H1 and EZH2 was up-regulated in patients with a history of ART. Additionally, we found that expression of SIRT1 can protect cardiomyocytes in presence of ARV drugs through reduction of cellular ROS and cellular hypertrophy. Our results reveal that ARV drugs modulate the epigenetic histone markers involved in gene expression, and play a critical role in histone deacetylation at H3K9 and H3K27 during cellular stress. This study may lead to development of novel therapeutic strategies for the treatment of CVD in PLWH.